Design and stress analysis of adjustable chair on handcycle for persons with disabilities - Andika Wisnujati (Jurnal POLIMESIN, 2022)
Handcycle is one of bicycle that used by someone with physical limitations, and this bicycle is operated by hand.  Some people who have physical limitations will not be able to ride a bicycle in general, so a handcycle is made using three wheels to be able to maintain the balance of the rider's body. This handcycle is a solution for people with disabilities to be able to go somewhere and also exercise. In this study, an adjustable chair design was made that is suitable for handcycles and has an adjustable function, namely making the handcycle seat move forward or backward to make it easier for a rider to adjust the position of the legs in moving the handcycle. The material used to manufacture the adjustable chair on the handcycle is iron plate, which is an elbow-shaped iron plate with an angle of 90o. The length is 300 mm, width 200 mm and thickness 50 mm. After the design is made, then a stress analysis test with Autodesk Inventor 2016 is carried out on the adjustable chair on the handcycle by analyzing the strength of the chair and also the appropriate body posture when supporting the weight of a person with a disability. The final result of the adjustable chair applied to the handcycle was measured by stress analysis using Autodesk Inventor 2016 software. The material strength (Von Misess) for male users who weighs 70 kg has a maximum value of 1.767 MPa with a maximum displacement of 0.0059. As for female users weighing 60 kg, the maximum value is 1.514 MPa with a maximum displacement of 0.050.